A Subtitling Analysis Of Verb And Verb Phrase Found InThe Magic Of Belle Isle - ASTUTIK, INDAH HENDRI, Dr. Dwi Haryanti, M.Hum, Nur Hidayat, M. Pd (2016)
The objectives of this study are to classify subtitling shift of verb and verb phrase found in The Magic of Belle Isle and to describe subtitling accuracy of The Magic of Belle Isle. The type of this study is descriptive qualitative. For the first objective of the study, the data are sentences containing verb and verb phrase found in The Magic of Belle Isle. While for the second objective of the study, the data are sentences of utterance found in The Magic of Belle Isle. There are 1283 data found that match with the classification of the shift. Firstly, based on the data of verb's translation, it is found that there is class shift where verbs are translated into nouns, adjectives, adverbs, pronouns, and preposition. The data that match the level shift are verbs translated into verb phrases, and into noun phrase. The data that match with intra-system shift are V+s translated into verb, V+es translated into verb, V+ed in V2 form translated into verb, V+ed in V3 form translated into verb, V+ing translated into verb, and verbs translated into reduplication verbs. Secondly, based on the data of verb phrase's translation, it is found that there is class shift where verbs phrases are translated into noun phrase and adjective phrase. The data that match with level shift are verb phrases translated into nouns, verb phrases translated into verbs, verb phrases translated into adjectives, verb phrases translated into adverbs, and verb phrase translated into pronoun. There is also structure shift found. The second result of this study shows that there are 1525 data found and dealt with accuracy. It is found that 1515 data (99.3%) are accurately translated, 6 data (0.4%) are less accurately translated, and 4 data (0.3%) are inaccurately translated. Keywords: subtitling, translation, translation shift, translation accuracy